Using Social Stories to Decrease Negative Behaviors in Students with Autism and Other Disabilities - Williams, Vivian C. (Journal of the American Academy of Special Education Professionals, 2021)
Social stories are effective interventions that can be used to manage negative behaviors and develop social skills. However, contradictory results are suggested within the research because of variability in designing social stories, intervention phases, target behaviors, and treatment protocol. Social story interventions may reduce negative behaviors among many children and adolescents with autism, other pervasive developmental disorders, and emotional and behavioral disabilities. Many research studies focused on the implementation of social stories with children and adolescents who range from 3-15 years of age. From these studies, social stories were found to be an effective intervention for increasing appropriate behaviors and decreasing challenging behaviors. This paper examines current research in the use of social stories’ intervention to reduce negative behaviors for students with autism and other disabilities.